Pola Pemanfaatan Remitan (Remittance) Perantau Nagari Atar, Kabupaten Tanah Datar, Provinsi Sumatera Barat - Fitri Yolanda (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2020)
Abstract : Remittances from migrants are one of the potentials that can be utilized by the village to improve welfare. Atar is one of the nagari which has a large number of guides in various cities in Indonesia. The problem raised in this study is to see how the pattern of use of remittances from migrants for Nagari Atar. The objectives of this research are; 1.) Describe the pattern of use of remittances from migrants at the household level and 2.) Describe the patterns of use of remittances from migrants for the development of Nagari Atar. As an analytical tool, the structuration theory proposed by Anthony Giddens is used. This study used a qualitative approach using in-depth interviews and observation as data collection tools. The results of this study indicate that the frequency of money transfers is uncertain and is sent only when there is a need. Meanwhile, the frequency of sending goods is sent during the new school year and Eid. Economic remittances are like money and goods, while social remittances are in the form of ideas and main ideas for village development. The pattern of using remittances at the family level is divided into the use of family consumptive remittances and the use of family productive remittances. The use of remittances at the village level is for the physical development of the village and the non-physical development of the village.